Optimization of synthesis parameters for copper oxide-enhanced phase change material: Balancing thermal conductivity and latent heat trade-off - Mohan, Man; Josline, Mukkath Joseph; Nagarjuna, Cheenepalli; Dewangan, Sheetal Kumar; Sharma, Vinod Kumar; Kannan, K. Gopi; Rao, K. Raja; Lee, Jae Hyun; Lee, Kwan; Ahn, Byungmin (Thermal Science and Engineering Progress, 2025)
Phase change materials (PCMs) offer immense potential for thermal energy storage owing to their superior latent heat storage properties. However, their low intrinsic thermal conductivity restricts efficient heat transfer, posing a significant challenge to practical applications. The integration of nanoparticles to create nano-enhanced phase change materials (NePCMs) has proven effective in addressing this limitation, though it often introduces a trade-off in latent heat storage capacity. This study presents an optimized synthesis strategy for NePCMs using a hybrid approach combining Taguchi and response surface methodology (RSM). Unlike conventional methods, this approach concurrently improves thermal conductivity and latent heat capacity by systematically analyzing the influence of synthesis parameters. The quantitative impact of each synthesis parameter on thermal conductivity and latent heat is evaluated to facilitate targeted optimization. The methodology achieved a composite desirability of 82.5 %, reflecting substantial concurrent enhancements. The optimized NePCM demonstrated a 48.5 % increase in thermal conductivity alongside latent heat increases of 29.1 % during melting and 15.6 % during solidification compared to pure PCM, offering a significant advancement in overcoming the thermal conductivity-latent heat trade-off.
Keywords: Latent heat storage; Optimisations; Particles sizes; Phase Change; Response-surface methodology; Storage capacity; Synthesis parameters; Taguchi; Thermal; Trade off; Latent heat; Optimization; Particle size; Phase change material; RSM; Sonication; Storage capacity; Taguchi; Thermal conductivity